Decolorization Of Dye Pollutants By Fenton-Like Oxidation Process Using Zeolite And Natural Clay Based Catalysts - Hassan, Hamizura (2010)
The decolorization of Acid Red 1 (AR1) and Reactive Blue 4 (RB4) dye by the Fenton-like oxidation process using zeolite and natural based catalysts in batch system were studied. Fe-zeolite Y type (Fe-ZYT), Fe-natural zeolite (Fe-NZ), Fe-ball clay (Fe-BC), and Fe-Kuala Kangsar clay (Fe-KKC) were successfully prepared via impregnation method. The prepared catalysts were characterized by Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-ray powder diffraction (XRD), Nitrogen adsorption/desorption and Energy Disperse X-ray (EDX).